2005
DOI: 10.1088/0022-3727/38/17/s09
|View full text |Cite
|
Sign up to set email alerts
|

Infrared continuum radiation from high and ultra-high pressure mercury lamps

Abstract: Infrared (IR) continuum radiation from the arc of high and ultra-high pressure (UHP) mercury lamps was measured and modelled. Three major contributions to the IR continuum are electron–atom bremsstrahlung, which is dominant, electron–ion bremsstrahlung and electron–ion recombination radiation. The line width of the resonance broadened Hg 71S0 to 61P1 transition at 1014 nm was used to determine the arc core Hg density, and the radiance of this line was used to determine the arc temperature as a function of radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…19 The axis temperature T = 8270 K came from a radiance measurement; the range of 8200-8300 K for this lamp was confirmed on several Hg lines and with two experimental setups. 10 Recently, Kane et al 6 confirmed this p value by a Brewster-angle reflection measurement of n at the inner wall and an estimate of the local T based on pyrometry of the outer wall. They found 20.1͑1.1͒ MPa for a lamp of the same type; the difference of 6% can be due to production tolerances but also to a quartz-tube shielding in the first experiment that may well have increased the pressure slightly by raising the temperature of the arc tube.…”
Section: B Comparison To Other Uhp Pressure Measurementsmentioning
confidence: 91%
See 3 more Smart Citations
“…19 The axis temperature T = 8270 K came from a radiance measurement; the range of 8200-8300 K for this lamp was confirmed on several Hg lines and with two experimental setups. 10 Recently, Kane et al 6 confirmed this p value by a Brewster-angle reflection measurement of n at the inner wall and an estimate of the local T based on pyrometry of the outer wall. They found 20.1͑1.1͒ MPa for a lamp of the same type; the difference of 6% can be due to production tolerances but also to a quartz-tube shielding in the first experiment that may well have increased the pressure slightly by raising the temperature of the arc tube.…”
Section: B Comparison To Other Uhp Pressure Measurementsmentioning
confidence: 91%
“…Lawler et al 10 determined a pressure of 21.3 MPa for a commercial Philips UHP lamp ͑120 W, 1.0 mm arc gap͒ at vertical operation from measurements of the Hg number density n and the local temperature T on the arc axis. The density n = 1.87ϫ 10 26 m −3 was derived from the measured width of the 1014 nm Hg line whose resonance broadening is well understood.…”
Section: B Comparison To Other Uhp Pressure Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Infrared radiation, either in the form of radiation from the plasma or in the form of thermal radiation from the burner wall, can consume 50-75% of the total input power. The ALITE-II project's [6] primary focus was the infrared radiation of HID lamps; several papers regarding the infrared radiation from HID lamps have recently been published [7][8][9]. In these papers the focus was mainly on the continuum radiation generated by the plasma.…”
Section: Introductionmentioning
confidence: 99%